The Nigerian textile industry - African Development Consulting Group (Lagos : African Development Consulting Group, 1994)
The primary purpose of this survey is to explore and identify the potentials for the growth and development of the Nigerian textile industry, its markets and future prospects as well as its ascendant problems.
ne 18/04/2019
Ref
Keywords: Textile industry; Nigeria